Oil body extraction from oleo-proteaginous seeds and conservation of valuable native compounds☆ - Fabre Jean-François; Lacroux Eric; Cerny Muriel; Vaca-Medina Guadalupe; Cassen Audrey; Merah Othmane; Valentin Romain; Mouloungui Zéphirin (Oilseeds and fats, crops and lipids, 2023)
Oil bodies, also called oleosomes have been the object of an increased interest since the last decade. Different processes of extraction and purification involve an aqueous crushing with methods to soften the cell membranes. An integrated process was used on different oilseeds to compare the different oil-body dispersions obtained. Once extracted with an aqueous crushing, oil bodies are dispersed in a creamy phase containing also an important protein content. Their stability depends on membranous proteins but also surrounding, extraneous ones. To eliminate these non-membranous proteins, the emulsion can be washed with different compounds allowing a good protein solubilization. If the fatty acid, phytosterol, tocopherol contents and distribution are compared between seeds and dispersions of oil bodies, there appears to be little significant change. These valuable compounds are hence preserved in the oil bodies. However, aqueous crushing releases phospholipase partly explaining the lower phospholipid content and the higher relative concentration of phosphatidic acid. To preserve these emulsions, it is possible to dry them either through freeze-drying or spray-drying. Spray-drying allows a better recovery of the physical structure of the emulsion after rehydration but cryo-protectants as Tris or Glycerol can limit emulsion degradation provoked by hard mechanical constraints of a freeze-drying process.